Tata Kelola Pariwisata Berkelanjutan: Studi Kasus Danau Lau Kawar, Desa Kuta Gugung, Kecamatan Naman Teran, Kabupaten Karo - Khadry, Muhammad; Putri, Risyah Andira; Sembiring, Hudan Breby Br; Damanik, Astri Perisay; Zahro, Siti (Tourism, Hospitality And Culture Insights Journal, 2025)
North Sumatra is a province with significant potential derived from its natural, cultural, and man-made attractions, among which Lau Kawar Lake stands out as a notable tourist destination. Located in Karo Regency, Lau Kawar Lake has been providing benefits to the local community. Given that Lau Kawar Lake has become a promising tourism sector capable of boosting the surrounding economy, its development must also consider the social and environmental issues that may arise, thus necessitating the adoption of sustainable tourism concepts. Sustainable tourism can be implemented using various indicators, one of which is the Global Sustainable Tourism Council (GSTC) criteria. By employing a qualitative descriptive methodology, including data collection through interviews, field observations, and documentation, this research aims to understand the management of Lau Kawar Lake as a tourist destination and identify the challenges faced in its management in accordance with GSTC criteria. The research findings indicate that the management practices at Lau Kawar Lake largely do not align with the sustainable tourism indicators set forth by the GSTC. Based on observations using the GSTC sustainable management framework, the overall sustainability management of Lau Kawar Lake remains poor. The insights gained from this study can provide valuable information for developing Lau Kawar Lake to meet the requirements of becoming a sustainable tourism destination.